Viability Status-Dependent Effect of Bifidobacterium longum ssp. longum CCM 7952 on Prevention of Allergic Inflammation in Mouse Model - Pyclik, Marcelina Joanna; Srutkova, Dagmar; Razim, Agnieszka; Hermanova, Petra; Svabova, Tereza; Pacyga, Katarzyna; Schwarzer, Martin; Górska, Sabina (Frontiers in Immunology, 2021)
The classical definition of probiotics states that bacteria must be alive to be beneficial for human organism. However, recent reports show that inactivated bacteria or their effector molecules can also possess such properties. In this study, we investigated the physical and immunomodulatory properties of four Bifidobacterium strains in the heat-treated (HT) and untreated (UN) forms. We showed that temperature treatment of bacteria changes their size and charge, which affects their interaction with epithelial and immune cells. Based on the in vitro assays, we observed that all tested strains reduced the level of OVA-induced IL-4, IL-5 and IL-13 in the spleen culture of OVA-sensitized mice. We selected Bifidobacterium longum ssp. longum CCM 7952 (Bl 7952) for further analysis. In vivo experiments confirmed that untreated Bl 7952 exhibited allergy-reducing properties when administered intranasally to OVA-sensitized mice, which manifested in significant suppression of airway inflammation. Untreated Bl 7952 decreased local and systemic levels of Th2 related cytokines, OVA-specific IgE antibodies and simultaneously inhibited airway eosinophilia. In contrast, heat-treated Bl 7952 was only able to reduce IL-4 levels in the lungs and eosinophils in bronchoalveolar lavage, but increased neutrophil and macrophage numbers. We demonstrated that the viability status of Bl 7952 is a prerequisite for the beneficial effects of bacteria, and that heat treatment reduces but does not completely abolish these properties. Further research on bacterial effector molecules to elucidate the beneficial effects of probiotics in the prevention of allergic diseases is warranted.